Optimalisasi Fermentasi Bioetanol Campuran Batang Pisang (Musa paradisiaca) dan Bonggol Jagung (Zea mays) dengan Variasi Perlakuan dan Waktu - Khairul Hidayah; Endang Widi Winarni; Rendy Wikrama Wardana; M. Lutfi Firdaus; Hayuni Retno Widarti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to determine the ethanol content from banana stem and corn cob residues with variations in treatment and fermentation time using a starter culture to accelerate the fermentation process. The method used was an experimental design with treatment variations and fermentation times of 9, 12, and 15 days. Quantitative data were analyzed by measuring the average ethanol content and volume produced for each treatment and fermentation time, then presented in graphical form. The results showed that the highest ethanol content was obtained in treatment A (100% yeast) with 20% ethanol after 15 days of fermentation. In conclusion, the longer the fermentation time, the higher the ethanol content; however, the effect of fermentation time was not always consistent because ethanol content is influenced by the materials used, fermentation duration, and the condition of microorganisms during the fermentation process. Keywords: Banana Stem Residues, Bioethanol, Corn Cob Residues, Environmentally Friendly Technology